2016
DOI: 10.15740/has/au/11.2/158-162
|View full text |Cite
|
Sign up to set email alerts
|

Scale to measure attitude of the farmers towards greenhouse technology (GT)

Abstract: SUMMARY :A scale was developed to measure the attitude of the farmers towards greenhouse technology based on "Scale Product Method" which combines the Thurston's technique of Equal Appearing Interval Scale for selection of the items and Likert's techniques of summated rating for ascertaining the response on the scale. A tentative list of 33 statements was drafted keeping in view the applicability of statements suited to the area of study. The statements collected were edited in the light of the criteria sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The costs of farm inputs such as seeds, fertilisers, pesticides have been cited elsewhere as a major hindrance to the adoption of greenhouse technology (Wayua et al, 2020). A similar finding was reported by Smitha et al (2016), who observed that non-availability and the cost of inputs for greenhouse production were major constraints faced by the farmers.…”
Section: High Cost Of Inputssupporting
confidence: 60%
See 3 more Smart Citations
“…The costs of farm inputs such as seeds, fertilisers, pesticides have been cited elsewhere as a major hindrance to the adoption of greenhouse technology (Wayua et al, 2020). A similar finding was reported by Smitha et al (2016), who observed that non-availability and the cost of inputs for greenhouse production were major constraints faced by the farmers.…”
Section: High Cost Of Inputssupporting
confidence: 60%
“…Such constraints suggest a need for accessible credit facilities. The current observation indicates that the smallholders are unable to access finances for the maintenance of their GH farming activities (Smitha et al, 2016). The authors further observed that the nonavailability of credit in time hampered GH-based farming among smallholders.…”
Section: Lack Of Finances For Maintenance/ Sustenance Of Greenhouse T...mentioning
confidence: 56%
See 2 more Smart Citations